Nutritional needs of elite endurance athletes. Part II: Dietary protein and the potential role of caffeine and creatine - Tarnopolsky, M. A.; Gibala, M. J.; Jeukendrup, A. E.; Phillips, S. M. (European Journal of Sport Science, 2005)
Amino acids contribute between 2-8% of the energy needs during endurance exercise. Endurance exercise training leads to an adaptive reduction in the oxidation of amino acids at the same absolute exercise intensity, however, the capacity to oxidize amino acids goes up due to the increase in the total amount of the rate limiting enzyme, branched chain 2-oxo-acid dehydrogenase. There appears to be a modest increase (range?=?12-95%) in protein requirements only for very well trained athletes who are actively training. Although the majority of athletes will have ample dietary protein to meet any increased need, those on a hypoenergetic diet or during extreme periods of physical stress may need dietary manipulation to accommodate the need. Caffeine is a trimethylxanthine derivative that is common in many foods and beverages. The consumption of caffeine (3-7 mg/kg) prior to endurance exercise improves performance for habitual and non-habitual consumers. The ergogenic effect is likely due to a direct effect on muscle contractility and not via an enhancement of fatty acid oxidation. Creatine is important in intra-cellular energy shuttling and in cellular fluid regulation. Creatine monohydrate supplementation (20 g/d X 3-5 days) increases fat-free mass, improves muscle strength during repetitive high intensity contractions and increases fat-free mass accumulation and strength during a period of weight training. Given the increase in weight, there are likely neutral or even performance reducing effects in sports that are influenced by body mass (i.e., running, hill climbing cycling).